Development Web-Based Inventory And Customer Management System For Retail Bakery Online - Liew, Chee Chung; Alduais, Nayef (Applied Information Technology And Computer Science, 2022)
Maggie Pastry, a retail bakery online founded by Maggie in 2020 during covid-19 pandemic. The inventory management process of the bakery is handled manually. Hence, there will be many uncontrollable human errors occurred. The two main problems cause by the above situation are hard prediction for the inventory level of baking ingredients and lack of customer service. Therefore, a web-based inventory and customer management system is proposed by using iterative development model. The proposed system was developed by using PHP language, AJAX technique, jQuery and SQL. MySQL was used as database management system while Visual Studio Code was used as text editor. The management process in a bakery done by system is familiar nowadays. The system can assist them by automating most of the repetitive tasks. In future, the automation in the system will be keep improved until fewer human resources are required in the process of management.